2022
DOI: 10.3390/ijerph192114492
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Depressive Symptoms, Rumination, and Suicide Ideation in Patients with Depression

Abstract: The relationship between suicide and rumination in depression is a recent topic of attention in mental health. The purpose of this study was to investigate the relationship between demographic variables, depressive symptoms, rumination, and suicide ideation in patients with depression, as well as the predictors of suicide ideation. Research design: A cross-sectional study of 95 subjects with depression recruited intentionally from the psychiatric ward of Tzu Chi Hospital. The questionnaire included demographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Our results are consistent with numerous earlier studies in the general population (Chiang et al, 2022; Wang et al, 2017) as well as those in the SCI population that support a significant relationship between depressive symptom symptomatology and SI (Charlifue & Gerhart, 1991; McCullumsmith et al, 2015). In the current study, participants who endorsed recent SI reported “moderate” depressive symptom severity, on average, compared to “minimal” depressive symptom severity by those who did not report SI.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with numerous earlier studies in the general population (Chiang et al, 2022; Wang et al, 2017) as well as those in the SCI population that support a significant relationship between depressive symptom symptomatology and SI (Charlifue & Gerhart, 1991; McCullumsmith et al, 2015). In the current study, participants who endorsed recent SI reported “moderate” depressive symptom severity, on average, compared to “minimal” depressive symptom severity by those who did not report SI.…”
Section: Discussionsupporting
confidence: 93%
“…This study revealed a link between depression and suicide (P value: 0.00; OR; 4,934), i.e., the more severe the level of depression, the higher the Suicide idea; in addition, people with high depression 4,934 times higher Suicide ideas. This study's results align with previous studies that revealed depression has a strong influence on Suicide ideas (Chiang et al, 2022;Ipung Jatmiko, 2019;Keilp et al, 2012;Shiraly et al, 2022). Another study identified that depression was higher in youngest-old adults with loss of health, economy, and role (Lee et al, 2014).…”
Section: Discussionsupporting
confidence: 89%
“…According to the Blue Book on Mental Health in China 2022, the detection rate of depression among adolescents in China was 15-20% in 2022. These negative and painful feelings accompanying depression, which are considered high risks of suicidal ideation, tend to cause individuals to generate suicidal ideation and even commit suicide [39,40]. Moreover, relevant empirical evidence has been accumulated that depression would increase the risk of self-injury, attempted or completed suicide, and other risky behaviors [41][42][43][44][45].…”
Section: The Mediating Role Of Depressionmentioning
confidence: 99%